2004
DOI: 10.1177/014556130408300914
|View full text |Cite
|
Sign up to set email alerts
|

Second Branchial Cleft Anomaly Presenting as a Rudimentary Pinna in the Nasopharynx of a Newborn

Abstract: Wedescrib e the ease of a 4-day -o/d girl who presentedwith an epig /ottie eyst that was later identified as a rudimentary p inna attaehed to the soft pa/ate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The most common congenital upper-airway malformations include craniofacial dysmorphology (micrognathia, glossoptosis), choanal atresia, macroglossia, subglottic stenosis , congeni tal cysts of the nasopha rynx [3], dacryoc ystocele [4,5], the b hairy polyp Q of the ph arynx [6,7], anomalies related to the second, third, or fourth branchial arches [8][9][10] , and broncho genic cyst of the orophar ynx and hypophar ynx [11]. Somet imes, as in our pati ent, a mucosal oropharyngeal cyst is found in an otherwise healthy child.…”
Section: Discussionmentioning
confidence: 99%
“…The most common congenital upper-airway malformations include craniofacial dysmorphology (micrognathia, glossoptosis), choanal atresia, macroglossia, subglottic stenosis , congeni tal cysts of the nasopha rynx [3], dacryoc ystocele [4,5], the b hairy polyp Q of the ph arynx [6,7], anomalies related to the second, third, or fourth branchial arches [8][9][10] , and broncho genic cyst of the orophar ynx and hypophar ynx [11]. Somet imes, as in our pati ent, a mucosal oropharyngeal cyst is found in an otherwise healthy child.…”
Section: Discussionmentioning
confidence: 99%
“…A rudimentary pinna of second arch origin-attached to both the epiglottis and soft palate without associated cyst, sinus, or fi stulahas been described. 9 Ada et al presented a Work type I anomaly which, although stemming from the external auditory canal, extended into the nasopharynx via a tympanic membrane perforation and the eustachian tube. 22 Pathology revealed a 1.8 × 1.1 × 0.4-cm mass with squamous mucosa, clusters of seromucinous glands and ducts, reactive lymphocytic hyperplasia with occasional germinal centers, and interspersed chronic infl ammatory cells including plasma cells and lymphocytes.…”
Section: Case Reportmentioning
confidence: 99%
“…In our review of the medical literature, we found a number of case reports with unusual presentations of BAs, including retropharyngeal abscesses, 2,3 pharyngoceles, 4 duplicate ossicles, 5 intrathryoidal lesions, [6][7][8] an epiglottic cyst, 9 and 2 cases of pharyngeal branchial cysts involving the tonsil. 10 We found two reports of cases involving the oropharynx, 11,12 but no reports of a BA presenting as a posterior oropharyngeal mass, as in our case.…”
Section: Introductionmentioning
confidence: 99%
“…Accessory auricular abnormalities can occasionally be found in the nasopharynx 2,3 , middle ear 4 , and the neck.…”
Section: Introductionmentioning
confidence: 99%